Describing electronic, digital, and other media using AACR2 and RDA : a how-to-do-it manual and CD-ROM for librarians - Weber, Mary Beth.; Austin, Fay Angela (New York : Neal-Schuman Publishers, 2011)
The book provided a useful information and ideas for catologers who are charged with creating descriptive records in the rapidly changing environment of resource description for digital and nontangible formats, by guiding step-by-step instructions for the creation of descriptive records based on its principles.
Essential background -- Cartographic resources -- Sound recordings -- Videos -- Electronic resources -- Electronic integrating resources -- Microforms -- Multimedia kits and mixed materials.
Includes bibliographical references and index.
uaj 07/05/13
Loan
Keywords: Cataloging of nonbook materials -- Handbooks, manuals, etc; Cataloging of audio-visual materials -- Handbooks, manuals, etc; Cataloging of electronic information resources -- Handbooks, manuals, etc; Descriptive cataloging -- Standards